Aggregation of silver nanoparticles in natural seawater - Dou Lianyu; Yan Zhiyong; Wang Chu (E3S Web of Conferences)
The metal-based nanoparticles in seawater posed significant threats to marine ecosystems. This study investigated the aggregation of silver nanoparticles (AgNPs) in natural seawater. Results demonstrated that the aggregation of Ag NPs decreased with the increase of TOC concentration, while increased with turbidity. Linear regression analysis revealed a statistically significant correlation between the concentration of TOC and the hydrodynamic diameter of Ag NPs (P < 0.05). The results provided critical insights into the transport and fate of AgNPs in marine environments.